Endodontic Microbiology-A Special Issue of Dentistry Journal - Prasanna Neelakantan (MDPI AG, 2018)
Understanding microbiology, specifically biofilm biology is an essential component of creating targeted therapeutic modalities that are effective and efficient.[...]